A prospective pilot study of the effect on catecholamines of mindfulness training vs pharmacological prophylaxis in patients with chronic migraine and medication overuse headache. (April 2019) - Grazzi, Licia; Raggi, Alberto; D'Amico, Domenico; Sansone, Emanuela; Leonardi, Matilde; Andrasik, Frank; Gucciardi, Antonina; Guido, Davide; D'Andrea, Giovanni
Aim: To address whether, in patients with chronic migraine and medication overuse headache, mindfulness-based treatment is associated with changes in plasma levels of catecholamines and elusive amines that are similar to those observed in patients undergoing pharmacological prophylaxis. Methods: In this non-randomized, clinic-based effectiveness study, patients aged 18–65, with a history of chronic migraine ≥ 10 years and overuse of triptans or non-steroidal anti-inflammatory drugs ≥ 5 years, were enrolled. Upon completion of a structured withdrawal program, patients received either pharmacological prophylaxis or six weekly sessions of mindfulness-based treatment and were followed for 12 months. Daily headache diaries were used to record headache frequency and medication intake; catecholamines (noradrenaline, epinephrine and dopamine) and levels of elusive amines were assayed from poor platelet plasma. Results: Complete follow-up data were available for 15 patients in the pharmacological prophylaxis-group (14 females, average age 44.1) and 14 in the mindfulness treatment-group (all females, average age 46.4), and all variables were comparable between groups at baseline. At 12 months, significant improvement ( p  < .001) was found in the pharmacological prophylaxis group for headache frequency and medication intake (by 51% and 48.7%, respectively), noradrenaline, epinephrine and dopamine (by 98.7%, 120.8% and 501.9%, respectively); patients in the mindfulness treatment-group performed similarly. For elusive amines, no longitudinal changes were found. Conclusions: The similar improvement trends observed in the two groups of patients further support the utility of mindfulness-based treatment in migraine care, and reinforce the hypothesis that alteration and normalization of tyrosine metabolism are implicated in migraine chronification and in remission of chronic migraine.